2020
DOI: 10.1007/s10549-020-06008-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and breast cancer at a Regional Breast Centre: our flexible approach during the pandemic

Abstract: Purpose In British Columbia (BC), there have been 2790 confirmed COVID-19 cases as of June 20, 2020. The aim of this project is to capture the effect of COVID-19 on the volume of surgery and adaptations to the surgical care of patients at a breast centre in BC. Methods All proven or suspected breast cancer cases treated with surgery between March 16, 2019 and April 30, 2019 and March 16, 2020 and April 30, 2020 through the Providence Breast Centre were included in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 3 publications
7
64
0
2
Order By: Relevance
“…Nearly all studies offered guidance on how to perform breast reconstruction during the pandemic; however, only 10 studies discussed the development of specific protocols. 14 , 16 , 18 , 20 , 24 , 26 , 27 , 30 , 34 , 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all studies offered guidance on how to perform breast reconstruction during the pandemic; however, only 10 studies discussed the development of specific protocols. 14 , 16 , 18 , 20 , 24 , 26 , 27 , 30 , 34 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…These protocols involved assessment of patient variables such as age, breast cancer characteristics, need for adjuvant therapy, and other comorbidities. 16 , 18 , 24 , 27 , 30 , 34 …”
Section: Resultsmentioning
confidence: 99%
“…The authors reported that 196 patients in 2020 compared with 129 patients in 2019 successfully underwent BCa surgery and noted significant adaptations that were implemented in response to the COVID-19 pandemic. They are of the opinion that increased access to telemedicine and better anesthetic techniques will significantly improve overall BCa surgical care during and beyond the COVID-19 pandemic [53]. Also, in a recent study Fregatti et al implemented a patient-tailored screening program that sought to prevent COVID-19 infection among health care workers and BCa patients undergoing surgery.…”
Section: Telehealth Covid-19 and Breast Cancer Surgerymentioning
confidence: 99%
“…Por esta razão, pacientes com câncer de mama e demais necessitam de um tratamento que equilibre o risco de progressão tumoral e de contaminação do coronavírus (Sorbo et al, 2020). Para isso, as adaptações perioperatórias incluíram a preferência por a AR (Cadili et al, 2021) para cirurgias emergenciais que apresentam alto risco de vida, classificadas em procedimentos de prioridade cirúrgica A e B (B1) (Holmes, 2020). Cadili et al (2020) avaliou o efeito da COVID-19 na quantidade e necessidade de adaptações a cirurgias de pacientes com câncer de mama na Columbia Britânica entre março a abril de 2019 e no mesmo período em 2020.…”
Section: Mastologiaunclassified
“…Isso implicou em uma diferença estatisticamente significante nas altas no mesmo dia da cirurgia, sendo de 68% em 2019 e 93% em 2020 (p =0,00001) e maior qualidade das cirurgias. Os autores concluem que a pandemia mudou o tratamento cirúrgico do câncer de mama para além da era pandêmica com a adoção de técnicas anestésicas mais seguras para os pacientes e profissionais da saúde (Cadili et al, 2021).…”
Section: Mastologiaunclassified